Use of Nanotechnology in Agri-food Sectors and Apprehensions: An Overview - SHIV K YADAV; SK LAL; S YADAV; J LAXMAN; B VERMA; MK SUSHMA; R CHOUDHARY; PK SINGH; SP SINGH; V SHARMA; BRIJRAJ SINGH (Seed Research, 2026)
The key challenge for the agriculture sector is to feed an ever-increasing global population with adoption of sustainable agricultural practices, integrating the goals of environmental health, economic profitability, and social equity. In this regard, nanotechnology is a globally rapidly growing ûeld of science and technology and casting an impact on every aspect of human life. It has also been recognized as one of its six “Key Enabling Technologies” by the European Commission, which contributes to sustainable competitiveness and growth in several industrial sectors. Considering the success of nanotechnology in different areas, application of nanoparticles (NPs) also started in agriculture but it is still in nascent phase. However, this could be a viable and sustainable option for instigating revolutionary changes in agricultural sector and the seed industry for delivering better outcomes in the coming years. Out of approx. 29000 patents on NPs granted worldwide, only 500 patents account for agriculture and nutrition aspects. Every year, several new nano-based agri-inputs and products are expected to be introduced into the market. Slowly but surely NPs are gaining attention of researchers, industry, end users and policy makers in India. The specific considerations for evaluation of NPs with a focus to address the issues regarding safe handling of nanofertilizers and nanopesticides (with or without nanocarriers) have been made in the recent guidelines from DBT in the context of Insecticide Act, Fertilizer Control Order, BIS and FSSAI. Hence, it would be interesting to use and carryout research on NPs, following new regulatory framework to be in place soon. Using nanomaterial as a carrier system for crop improvement and for enhancement of productivity would open new vistas for agriculture in the areas of pest/disease prevention, control and management, fertilizers, agrochemicals, biofertilizers and pheromones delivery, plant nutrients, anti-transpiration agents, plant growth regulators, biostimulants and plant genetic manipulation. Nanocarriers for nutraceutical delivery, nano processing aids, nanocomposites and nanosensors for safe applications in food, feed, packaging and dairy products would be gaining importance. NP based sensors could also have the potential to be employed as smart input delivery systems, determination of viability, losses, detection of seed borne pathogens in seeds and as growth monitoring, real time detection of pests, continuous monitoring of local environment etc. The results of nanoparticles used as seed priming agents to enhance seed germination, storage and crop productivity have been quite encouraging. Green synthesis protocols have gained extensive attention as a reliable, sustainable and eco-friendly means for the production of a wide range of nanomaterials. The researches on green NPs, their use in organic production and possibility of seed treatment applications have also been discussed in this. Since NPs are very infinitesimal in size and the quantity required for seed treatment purpose is still very less, it might not have an impact on flora and fauna above the threshold level. Still, the possible biosafety issues regarding use of NPs as seed treatment for improvement in seed germination, vigour and storability may arise. Considering the potential applications of NPs in many fields and the growing apprehensions of FDA about the toxic potential of nano products, it is need of the hour to look for new internationally agreed, unbiased toxicological models and focusing more on in vivo studies. Generally, science based evaluation of NPs and deliberations on the issues like; the possible ill effects of nano-particles on the environment, soil, plant nutrition and antagonistic effect on other nutrients, safety of workers, researchers, laboratory staff, seed industry and the health of general public, animals, insects and microbes etc. should only be the basis of policy decisions on NPs. The in-depth review of work done on mechanism and potential of nanoparticles in enhancing agricultural productivity and their possible impacts on ecosystem is also highlighted in this review.